PENGARUH PEMBINGKAIAN PESAN, INFORMASI KELANMGKAAN DAN PERBEDAAN INDIVIDUAL PADA SIKAP , NIAT DAN PERILAKU HEMAT ENERGI LISTRIK - , Indah Fatmawati, SE., Prof. Dr. Basu Swastha Dh., MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examined the effects of message framing in promoting electricity saving behavior among students. The model developed integrating prospect theory, scarcity theory and individual differences characteristic theory. The effect of message framing on participantsâ attitude and the interaction effects of scarcity information and need for cognition were examined. Laboratory experiments conducted with 2 (positive and negative framing) x 2 (given scarcity information and not given the scarcity information) x 2 (high NFC and low NFC) between subject factorial design. Participants were 288 student from 3 universities in Yogyakarta, Indonesia. Stimuli were given in the form of four pages booklet contained electricity saving message. Data analysis was performed using independent sample t test, two ways anova and logistic regression. The results do not support the hypotehsis of differential persuassive effects of message framing nor the interactionn effects of scarcity information and ned for cognition.mediation effects hypothesis of intention on attitude to influence behavior is supported in this study.